“It Makes Me Feel Like a Real Author”: Creating Multimodal, Digital Texts in an Elementary Writer’s Workshop - Moylan, Michael (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
This study explored multimodal literacies as it pertained to the use of digital technologies to create multimodal, digital texts within the scope of writer’s workshop in a fifth-grade classroom. The research was conducted from the viewpoint of sociocultural theory, multiliteracies, and New Literacies as writing is a social practice and communication is multimodal. Analysis of six classroom observations, student interviews, a student focus group, and a teacher interview indicate using multimodal literacies: (a) fosters high levels of engagement, (b) enhances meaning-making, (c) fosters opportunities for collaboration, (d) provides opportunities for publishing of professional-looking books for an authentic audience, and (e) fosters writing skills and writer identity.